PENGARUH SUHU DAN LAJU ALIR UDARA PENGERING PADA PENGERINGAN KARAGINAN MENGGUNAKAN TEKNOLOGI SPRAY DRYER - Ruben Tinosa Dwika; Trisna Ceningsih; Setia Budi Sasongko (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro,, 2012)
Carrageenan, as one of the treatment of seaweed, is very important role in food and beverage industry, pharmaceuticals, and others. The low quality of carrageenan in the state due to the less accurate drying system which is used as the final materials handling unit (finishing product). The method of spray dryer is drying the liquid by contacting the liquid droplets in the opposite direction or the direction of hot air. Humidity can be reduced by passing the air in the adsorbent column that will absorb moisture in it before entering the furnace room. Carrageenan with a spray drying process using zeolite as an absorbent of moisture is an alternative option to achieve an effective hot air. Variable used in this research was the temperature change of air for drying (70°C, 80oC, 90oC, 100oC) and a flow rate of air dryers (11 m / sec, 12 m / sec, 13 m / sec, 14 m / sec). The results showed that water content carrageenan products affected by temperature and air velocity dryer into the column. Carrageenan results with the lowest water content of 11.19% is achieved on the process conditions with a temperature of 100oC column with drying air velocity 14 m / sec. In addition, the heat transfer process (based on temperature) is more affected than the mass transfer processes of momentum transfer (based on drying air flow rate). As well, the efficiency of the drying process the product increases with increasing drying temperature and air velocity. The efficiency of the drying process the product for 83.33% carrageenan obtained at 100oC temperature conditions and the drying air velocity 14 m/sec.